Thermal conductivity of graphene nanoplatelets filled composites fabricated by solvent-free processing for the excellent filler dispersion and a theoretical approach for the composites containing the geometrized fillers - Kim, Seong Yun; Noh, Ye Ji; Yu, Jaesang (ELSEVIER SCI LTD, 2015)
The thermal conductivity of polymer composites containing nanofillers such as GNP (graphene nanoplatelet) and carbon black (CB) was investigated using experimental and theoretical approaches. We developed a fabrication method that allows different shapes and sizes of nanofillers to be highly dispersed in polymer resin. When the bulk and in-plane thermal conductivities of the fabricated composites were measured, they were found to increase rapidly as the GNP filler content increased. The in-plane thermal conductivity of composites with 20 wt.% GNP filler was found to reach a maximum value of 1.98 W/m K. The measured thermal conductivities were compared with the calculated values based on a micromechanics model where the waviness of nanofillers could be taken into account. The waviness of the incorporated GNP filler is an important physical factor that determines the thermal conductivity of composites and must be taken into consideration in theoretical calculations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: NANOCOMPOSITES; INTERFACE; FIELD; MOBILITY; MATRIX; ENERGY